Evaluating the yaws diagnostic gap: A survey to determine the capacity of and barriers to improving diagnostics in all yaws-endemic countries - Handley, Becca L.; Tchatchouang, Serges; Grout, Lise; Johnson, Roch Christian; Tabah, Earnest Njih; Boua, Bernard; Boock, Alphonse Um; Koffi, Aboa Paul; Phanzu, Delphin Mavinga; Kotey, Nana Konama; Rogers, Emerson; Dofitas, Belen; et al. (Frontiers in Tropical Diseases, 2022)
Background Yaws, caused by Treponema pallidum subsp. pertenue, is a skin neglected tropical disease. It is targeted for eradication by 2030, primarily using mass drug administration (MDA) with azithromycin. Traditionally, diagnosis of yaws has relied on clinical examination and serological testing. However, these approaches have poor diagnostic performance. To achieve eradication, more accurate diagnostics are required to determine whether MDA should be initiated or continued as well as for post-elimination surveillance. Molecular tools will be crucial for detecting antimicrobial resistant cases, which have the potential to derail eradication efforts. In order to determine the feasibility of introducing novel, more accurate, diagnostics for yaws surveillance purposes, it is necessary to understand current in-country diagnostic capacity. This study therefore aimed to understand the current capacity of, and challenges to, improving diagnostics for yaws in all yaws-endemic countries worldwide. Methodology/principal findings An online survey was sent to all 15 yaws-endemic countries in July 2021. The survey asked about past prevalence estimates, the availability of different diagnostic tools, and perceived barriers to enhancing capacity. Fourteen countries responded to the survey, four of which did not have a current National Policy for yaws eradication in place. Over 95% of reported that yaws cases from the past five years had not been confirmed with serological or molecular tools, largely due to the limited supply of rapid serological tests. Only four countries reported having operational laboratories for molecular yaws diagnosis, with only one of these having a validated assay to detect azithromycin resistance. Conclusions and significance This study highlights the diagnostic capacity constraints across all respondent countries. Countries are in need of access to a sustainable supply of serological tests, and development of molecular testing facilities. Sufficient sustainable funding should be made available to ensure that appropriate diagnostic tools are available and utilised.